Pengembangan Spot Wisata Edu-Construction Di Objek Wisata Embung Desa Banjarejo - Al Ansyorie, Mohammad Musthofa; Ariestadi, Dian; Rahayuningsih, Titi; I’dfi, Gilang; Mega Maharani, Nur Ira; Syahdandi, Alviando Galih (Jurnal Inovasi Teknologi dan Edukasi Teknik, 2023)
Banjarejo Village has a huge opportunity to become an educational tourism village and needs development. The development of a tourist attraction must have something interesting to see, feel and certainly different from those in other places. The tourist village area is still limited to the ideals of the government and the local village community. Another thing is the unavailability of an educational tourist spot design for the development of the Banjarejo Village tourist area. So, it is necessary to touch and apply science and technology for the purposes of developing educational tourism spots in Banjarejo Village. One of the educational tourism spots that is suitable to be realized in the Banjarejo Village reservoir is the Edu-Construction Tourism Spot. Where the spot provides knowledge about development, such as making pavilions, bridges, or small buildings that can be realized in the village barrier, and it is hoped that the village community can develop development independently. Desa Banjarejo mempunyai peluang sangat besar untuk menjadi desa wisata edukasi dan perlu pengembangan. Pengembangan suatu objek wisata harus memiliki sesuatu yang menarik untuk dilihat, dirasakan dan tentunya berbeda dengan yang ada ditempat lain. kawasan desa wisata masih sebatas cita-cita dari pemerintah dan masyarakat desa setempat. Hal lainnya adalah belum tersedianya suatu desain spot wisata edukasi untuk pengembangan kawasan wisata Desa Banjarejo. Sehingga perlu adanya sentuhan dan aplikasi IPTEKS untuk keperluan pengembangan spot wisata edukasi Desa Banjarejo. Salah satu spot wisata edukasi yang cocok direalisasikan pada embung Desa Banjarejo adalah Spot Wisata Edu-Contruction. Dimana spot tersebut memberikan pengetahuan mengenai pembangunan seperti pembuatan cara pembuatan gazebo, jembatan, ataupun bangunan kecil yang bisa direalisasikan diembung desa dan diharapkan masyarakat desa tersebut dapat mengembangkan pembanguanan secara mandiri.